A fourth-generation MIMO-OFDM broadband wireless system design,performance, and field trial results. - Sampath, H.
Increasing demand for high-performance 4G broadband wireless is enabled by the use of multiple antennas at both base station and subscriber ends. Multiple antenna technologies enable high capacities suited for Internet and multimedia services, and also dramatically increase range and reliability. In this article we describe a multiple-input multiple-output OFDM wireless communication system, lab test results, and field test results obtained in San Jose, California. These are the first MIMO system field tests to establish the performance of MIMO communication systems. Increased capacity, coverage, and reliability are clearly evident from the test results presented in this article
Keywords: 4G wireless; Internet; Capacity; Coverage; Design; Field trial; Fourth-generation MIMO-OFDM.; Broadband wireless system; Multimedia; Multiple antennas; Multiple input multiple-output communication system; Performance; Reliability